2018
DOI: 10.3389/fimmu.2018.01884
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into the Molecular Mechanisms of T Follicular Helper-Mediated Immunity and Pathology

Abstract: T follicular helper (Tfh) cells play key role in providing help to B cells during germinal center (GC) reactions. Generation of protective antibodies against various infections is an important aspect of Tfh-mediated immune responses and the dysregulation of Tfh cell responses has been implicated in various autoimmune disorders, inflammation, and malignancy. Thus, their differentiation and maintenance must be closely regulated to ensure appropriate help to B cells. The generation and function of Tfh cells is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 300 publications
3
77
0
Order By: Relevance
“…Tfh cells are essential for GC formation and maintenance, and provide survival signals for high affinity B cells within the GC for their differentiation to isotypeswitched antibody secreting cells and memory B cells 38,39 . Although the function of Tfr cells in the GC has not been completely clarified, the mainstream view currently is that Tfr cells restrict Tfh-and B-cell proliferation and exert an inhibitory action on antibody production [40][41][42] .…”
Section: Results 5: Pdl1 Blockage Does Not Affect the Ratio Of Tfh/tfrmentioning
confidence: 99%
“…Tfh cells are essential for GC formation and maintenance, and provide survival signals for high affinity B cells within the GC for their differentiation to isotypeswitched antibody secreting cells and memory B cells 38,39 . Although the function of Tfr cells in the GC has not been completely clarified, the mainstream view currently is that Tfr cells restrict Tfh-and B-cell proliferation and exert an inhibitory action on antibody production [40][41][42] .…”
Section: Results 5: Pdl1 Blockage Does Not Affect the Ratio Of Tfh/tfrmentioning
confidence: 99%
“…Accumulated studies have shown that follicular helper T cells (TFH) play an important role in assisting the immune function of human B cells. TFH is differentiated and developed from the initial CD4 + T cells in the germinal center (GC), and secretes IL-21 to promote self-proliferation and differentiation (9). TFH cells exist in the germinal center and peripheral blood, and circulating TFH can be divided into TFH1, TFH2, and TFH17 subsets, according to the expression of CXCR3 and CCR6 (10).…”
Section: Introductionmentioning
confidence: 99%
“…a Significant differences compared with that of the DC control, p < 0:001; b no significant differences compared with that of the LPS control, p > 0:05; c significant differences compared with that of the LPS control or Ad-shControl, p < 0:05. T cell-mediated immunity and pathology will also bring into many spotlight potential targets for novel cancer therapies [33]. In order to activate the full immunostimulatory talent of DCs, SIRPα which initiated a negative signal pathway to regulate the maturation of DCs was knocked down in this research.…”
Section: Discussionmentioning
confidence: 99%